Bioinformatic and mutational analysis of ophiovirus movement proteins, belonging to the 30K superfamily - Borniego, María Belén (2016)
Ophioviridae is a family of segmented, negative-sense, single-stranded RNA plant viruses. We showed that their cell-to-cell movement protein (MP) is an isolated member of the 30K MP superfamily with a unique structural organization. All 30K MPs share a core domain that contains a nearly-invariant signature aspartate. We examined its role in the MP of Citrus psorosis virus (CPsV) and Mirafiori lettuce big-vein virus (MiLBVV). Alanine substitution of this aspartate prevented plasmodesmata accumulation of MPMiLBVV, while MPCPsV was not affected. The capacity of ophiovirus MPs to increase the plasmodesmata size exclusion limit and non-cell autonomous protein feature was abolished in both mutants. To investigate the role of the signature aspartate in cell-to-cell movement, we constructed a new movement-deficient Tobacco mosaic virus vector used for trans-complementation assays. We showed that both ophiovirus MP mutants lack the cell-to-cell movement capacity, confirming that this signature aspartate is essential for viral cell-to-cell movement.